TEACHING MATHEMATICS TO ENGINEERING STUDENTS IN DEVELOPING COUNTRIES - Moussa, Nabil (European Scientific Journal, ESJ, 2014)
In this paper we discuss several aspects of teaching mathematics to engineering students in developing in countries taking into consideration the methods and strategies of teaching mathematics both at school level and higher education level in general and especially for engineering students. A proposal for measures to remedy the negative aspects of teaching in developing countries is then given.